Crafting effective oversight for the long-term storage of spent nuclear fuel on sites at risk of climate and coastal hazards - Brown, Alexander; Marlow, Jennifer; Sorfleet, Julie (Frontiers in Climate, 2024)
Despite a documented push to expand nuclear energy in the U.S., the status quo of indefinite in-situ nuclear waste storage is uncertain and increasingly threatened by climate and coastal hazards. Findings from Humboldt Bay, California, one of the nation’s most vulnerable nuclear storage sites, informed recommendations for managing emergent climate and coastal hazards. The existing legislative framework was not designed to address climate and nuclear waste interactions, but more effective oversight leveraging existing federal, state, local, and Tribal government authorities could adapt SNF management to a climate-changed world. More effective oversight requires updated regulations and site-specific risk assessments as well as enhanced coordination across jurisdictions, disciplines, and publics to increase legitimacy, trust, accountability, and creativity in light of failed solutions to a multi-decadal issue.